2001
DOI: 10.1002/1096-8628(20010115)98:2<185::aid-ajmg1029>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial and dental characteristics of Kabuki syndrome

Abstract: We describe oral manifestations in six patients (three females and three males aged 6 to 24 years) with Kabuki syndrome (KS), based on their physical, orthopantomographic, and cephalometric findings. All six patients had a high-arched palate, malocclusion, most commonly unilateral posterior cross-bite (5/6), severe maxillary recession and mid-facial hypoplasia. Other frequently observed oral manifestations included small dental arch and hypodontia. Three patients lacked permanent teeth, mostly the central/late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 8 publications
6
32
1
2
Order By: Relevance
“…In contrast with the findings from previous papers, 1,2,9–12,14,16,17,19 which reported that individuals with KMS typically present postnatal growth deficiency, this child had a stature compatible with his age. However, patients with KMS who have normal growth have also been described by others 5,6,16,17 . According to White et al, 27 low stature in people with KMS is actually less common than previously assumed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with the findings from previous papers, 1,2,9–12,14,16,17,19 which reported that individuals with KMS typically present postnatal growth deficiency, this child had a stature compatible with his age. However, patients with KMS who have normal growth have also been described by others 5,6,16,17 . According to White et al, 27 low stature in people with KMS is actually less common than previously assumed.…”
Section: Discussioncontrasting
confidence: 99%
“…Hypodontia and widely spaced teeth have been observed in over one‐third of the patient population with KMS 28 . Other typical oral manifestations in KMS include a high‐arched palate, missing teeth, malocclusion, microdontia, small dental arch, maxillary recession, and mid‐facial hypoplasia 10,11,16–19,21,24 . A recent article 20 reported on a young patient with KMS who had fusion and gemination in the primary dentition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C20orf133 was expressed in the mesenchymal components of the tooth-bud condensations at E14.5. Interestingly, dental anomalies such as hypodontia, malocclusion, microdontia and small dental arches, were seen in 68% of patients with KS in one study 48 , 49. Expression of the gene in the cells lining the vestibulocochlear and cochlear duct at stage E14.5, possibly explaining hearing loss, was reported in up to 82% of patients with KS 48.…”
Section: Discussionmentioning
confidence: 98%
“…Dental anomalies are seen in over 60% of patients with KS (33). The most common finding is hypodontia, particularly of the central and lateral incisors and the premolars.…”
Section: Manifestations By Organ Systemmentioning
confidence: 99%